A transient simulation approach to obtaining capacitance–voltage characteristics of GaN MOS capacitors with deep-level traps. (20th February 2018) - Fukuda, Koichi; Asai, Hidehiro; Hattori, Junichi; Shimizu, Mitsuaki; Hashizume, Tamotsu
Abstract: In this study, GaN MOS capacitance–voltage device simulations considering various interface and bulk traps are performed in the transient mode. The simulations explain various features of capacitance–voltage curves, such as plateau, hysteresis, and frequency dispersions, which are commonly observed in measurements of GaN MOS capacitors and arise from complicated combinations of interface and bulk deep-level traps. The objective of the present study is to provide a good theoretical tool to understand the physics of various nonideal measured curves.